(untitled) (Scientific journal of the Fergana State University, 2024)
The article philosophically analyzes the information about the founder of the Naqshbandi doctrine Bahauddin Naqshband, set out in the work ”Rubayati Khoja Naqshband", which has not been known to the general public until now.